Protective effect of Anoectochilus burmannicus extracts and its active compound, kinsenoside on adipocyte differentiation induced by benzyl butyl phthalate and bisphenol A - Pensiri Buacheen; Jirarat Karinchai; Natchapon Kammasit; Piya Temviriyanukul; Chutikarn Butkinaree; Santi Watthana; Ariyaphong Wongnoppavich; Arisa Imsumran; Pornsiri Pitchakarn (Scientific Reports, 2023)
Abstract Benzyl butyl phthalate (BBP) and bisphenol-A (BPA) are obesogens that have been reported to be associated with obesity. Inhibition of their adipogenic activity could decrease the risk of obesity-related metabolic disorders. This study hypothesized that Anoectochilus burmannicus ethanolic extract (ABE) which has been previously reported its anti-inflammation property and its known active compound, kinsenoside (Kin) abrogate BBP- and BPA-induced adipogenesis. ABE and Kin markedly suppress both BBP- and BPA-stimulated adipogenesis with different modulations on adipogenic-gene expression including C/EBPα, PPARγ, adiponectin, and leptin in 3T3-L1. BBP induced C/EBPα, adiponectin, and leptin mRNA expressions and slightly increased PPARγ mRNA level, whereas BPA markedly induced PPARγ and adiponectin mRNA levels. ABE significantly decreased the expression of C/EBPα and leptin, but not PPARγ and adiponectin in the BBP-treated cells. In the BPA-treated cells, ABE significantly decreased the mRNA expression of C/EBPα and PPARγ, but not adiponectin and leptin. Interestingly, Kin significantly overcame BBP- and BPA-induced C/EBPα, PPARγ, adiponectin, and leptin expressions. This study first provides evidence to support the health benefits of this plant, especially for people exposed to obesogens. Besides, this finding would encourage the conservation and culture of this orchid for development as an economic plant and healthy food.